STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA ANAK DURHAKA BATU KUTU DI KENAGARIAN SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Novrita, Delvi; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2019)
This study aims to describe: (1) the structure of legenda anak durhaka Batu Kutu in Kenagarian Surantih, Kecamatan Sutera, Kabupaten Pesisir Selatan. (2) social function of legenda anak durhaka Batu Kutu in Kenagarian Surantih, Kecamatan Sutera, Kabupaten Pesisir Selatan. This type of research is qualitative with descriptive methods. Data from this study is legenda anak durhaka Batu Kutu. The data collection technique was carried out in two stages, (1) the recording stage of legenda anak durhaka Batu Kutu, (2) collection of data on the storytelling environment. The results of this study can be concluded that the structure of folklore of legenda anak durhaka Batu Kutu consists of: (1) the style of language, the speech style of the language used by informants is the Minang language of the Surantih dialect. The language used is easy to understand, interesting, and contains aesthetic suggestions, (2) characterization, characters in legenda anak durhaka Batu Kutu consists of, the main characters, that are Puti and his two siblings and Amak, while the second characters in legenda anak durhaka Batu Kutu are Puti Husband. The characterization of each character is explained physically, psychologically, and social interaction, (3) background, background found in legenda anak durhaka Batu Kutu are place setting, time setting, and background setting, (4) the plot used in legenda anak durhaka Batu Kutu is a conventional plot, because the story starts from the early stages, middle stage and final stage, (5) theme, the theme of legenda anak durhaka Batu Kutu is the infidelity of three children to biological mother, (6) mandate, mandate inÂ of legend legenda anak durhaka Batu Kutu, that is, as a child may not be rebellious to parents, they should not argue with what parents say, and they must not hurt their parent. The social function of folklore of legenda anak durhaka Batu Kutu in Kenagarian Surantih, Kecamatan Sutera, Kabupaten Pesisir Selatan, that are: (1) educating, (2) inheriting oral traditions, and (3) as group identity.Â Keywords: folklore, Batu Kutu, social function